Feeding diets with graded levels of fermented soybean meal to Pacific whiteleg shrimp Penaeus vannamei (Boone, 1931): Effect on digestive enzymes, immune responses and carcass composition - Jannathulla, R.; Khan, H. Imran; Thulasi, D.; Kathyayani, S.; Ambasankar, K.; Panigrahi, A.; Muralidhar, M.; Dayal, J. Syama (Indian Journal of Fisheries, 2019)
A 45-days indoor trial was performed to assess the effect of fermented soybean meal (FSBM) on digestive enzyme activity, immune responses and carcass composition of amino acids, fatty acids, and minerals in Penaeus vannamei (Boone, 1931). Five iso-nitrogenous diets were formulated by replacing fishmeal (w/w) with FSBM (200, 250, 300. 350 and 400 g kg-1). A total of 300 juveniles (3.08Â±0.07 g) were randomly distributed to the experimental tanks at the rate of twenty shrimp per tank with three replications for each treatment. Protease activity (p